Fish welfare in farms: potential, knowledge gaps and other insights from the fair-fish database - Maia, Caroline Marques [UNESP]; Saraiva, João Luis; Gonçalves-de-Freitas, Eliane [UNESP] (Frontiers, 2024)
An adequate understanding of fish behaviors and their interaction with farm-specific environments is pivotal for enhancing fish welfare in aquaculture. The fair-fish database aims to provide a consistent overview of the welfare of farmed fish. This platform consolidates ethological knowledge into profiles of farmed aquatic species. Its WelfareCheck profiles are organized around welfare indicators, with each criterion receiving classifications (no findings, unclear, low, medium, and high) regarding the likelihood and potential for individuals of a given species to experience good welfare in aquaculture systems, along with the associated certainty level. These criteria include home range, depth range, migration patterns, reproduction, aggregation patterns, aggressive behavior, substrate needs, stress responses, malformations, and slaughtering protocols. We investigated which of these 10 criteria are most relevant to the overall welfare of a species, considering the likelihood, potential, and certainty of good welfare in aquaculture. To achieve this, we reviewed and recorded the high classifications across each criterion and dimension from all published WelfareCheck profiles. To further investigate knowledge gaps across the criteria, we also recorded classifications marked as unclear and no findings. These were then compared across the criteria to assess the frequency of such classifications. While no significant differences were found between the criteria regarding the likelihood that the surveyed species meet their basic welfare needs, criteria related to reproduction, slaughter practices, and substrate needs demonstrated a high potential for better welfare outcomes. Moreover, reproduction and migration patterns exhibited high certainty in the available literature. Based on these findings, we conclude that improving the reproduction of farmed aquatic species, considering their natural needs and behavior, could be an effective and reliable approach to improving welfare. However, we also found a low certainty of information on aggression and an absence or conflicting data on home range, aggregation patterns, stress, and malformations. This highlights an urgent need for research in these areas, which are fundamental for developing more accurate assessments and recommendations for farmed aquatic species.
Keywords: aquaculture; farmed fish; fish behavior; reproduction; welfare criteria